Linguistic and cultural adaptation into European Portuguese of swal-qol and swal-care outcomes tool for adults with oropharyngeal dysphagia - Antunes,Eva Bolle (2015)
Dysphagia can lead to symptoms like malnutrition, dehydration and aspiration pneumonia, and knowledge about the swallowing disorder can improve the patients quality of life. This paper reports the adaptation into European Portuguese of SWAL-QOL, which assesses the quality of life, and SWAL-CARE, for the quality of care, in swallowing disorders. The adaptation of SWAL-QOL and SWAL-CARE encompassed four steps, which were overseen by the researchers for clinical, linguistic and cultural equivalence: translation into European Portuguese; comparative review by a panel of experts; back-translation and approval by author of the original version; pre-test. After the discussion of specific concepts of the first translation, we had consensus version 1 in Portuguese, which was presented to the panel of experts. The resulting consensus version 2 was remitted for back-translation, then revised and compared with the original English surveys. Subsequently, the pre-test aimed to check the cultural equivalence, and the comprehension of the wording of the questions and the scales. The final version was obtained, after the researchers discussed some clinical and linguistic issues. SWAL-QOL-PT and SWAL-CARE-PT have linguistic as well as cultural equivalence with the original English version, and can be submitted to psychometric testing.